2012
DOI: 10.1002/med.21257
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Modulators of Keap1‐Nrf2‐ARE Pathway as Potential Preventive and Therapeutic Agents

Abstract: Keap1-Nrf2-ARE pathway represents one of the most important cellular defense mechanisms against oxidative stress and xenobiotic damage. Activation of Nrf2 signaling induces the transcriptional regulation of ARE-dependent expression of various detoxifying and antioxidant defense enzymes and proteins. Keap1-Nrf2-ARE signaling has become an attractive target for the prevention and treatment of oxidative stress-related diseases and conditions including cancer, neurodegenerative, cardiovascular, metabolic and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
595
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 677 publications
(606 citation statements)
references
References 269 publications
(398 reference statements)
7
595
1
3
Order By: Relevance
“…The recent evidence suggested that the involvement of ROS in HD pathogenesis is by dysfunctioning of the mitochondrial complex II (Calkins et al 2005). In the primary phase of HD, the focus is on the activation of the astrocyte and microglia by an overexpression of the vital cytoprotective genes via the Keap1-Nrf2-ARE system by Nrf2 agonist; this might protect the brain injury caused by the ROS (Magesh et al 2012). Activation of the Keap1-Nrf2-ARE pathway by small molecules in astrocytes accelerates the resistance of neurons to the non-excitotoxic glutamate toxicity (Kraft et al 2004).…”
Section: Huntington's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The recent evidence suggested that the involvement of ROS in HD pathogenesis is by dysfunctioning of the mitochondrial complex II (Calkins et al 2005). In the primary phase of HD, the focus is on the activation of the astrocyte and microglia by an overexpression of the vital cytoprotective genes via the Keap1-Nrf2-ARE system by Nrf2 agonist; this might protect the brain injury caused by the ROS (Magesh et al 2012). Activation of the Keap1-Nrf2-ARE pathway by small molecules in astrocytes accelerates the resistance of neurons to the non-excitotoxic glutamate toxicity (Kraft et al 2004).…”
Section: Huntington's Diseasementioning
confidence: 99%
“…The Keap1-targeted inhibition mechanism has been mainly carried out by inhibitors that could interrupt the cross-talk between the former and Nrf2 (Magesh et al 2012). One of the methodologies of reduction in the Keap1 population, hampering the redox balance, involves the dimerisation of Keap1 to prevent Nrf2 binding.…”
Section: Chemical Inhibitors Of Keap1mentioning
confidence: 99%
“…Organisms regulate the production and scavenging of free radicals spontaneously or passively via various signaling pathways. The nuclear factor erythroid-2-related factor 2 (Nrf2) pathway, a significant signaling pathway in the detoxification of ROS in the brain region [19,20] , represents an important cellular defense mechanism against oxidative stress damage [21] . This pathway controls an array of endogenous cellular defense mechanisms against oxidative stress [22] .…”
Section: Introductionmentioning
confidence: 99%
“…sulforaphane, chalcone, and curcumin. 12 These traditional Nrf2-ARE activators are all electrophiles that form a covalent bond to a cysteine residue in the target Keap1 protein. 13 The electrophilic nature of these activators could increase the uncertainty in further clinical development.…”
mentioning
confidence: 99%